Pengaruh Model Problem Based Learning Berbantuan Wordwall terhadap Hasil Belajar Matematika Materi Pecahan Peserta Didik Kelas V SDN 015 Samarinda Ulu - Yoga Afrizal Rifai; Sukriadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study was motivated by observations of low student learning outcomes in Mathematics, particularly in the topic of fractions. This condition is indicated to be caused by the dominant use of conventional teaching methods by teachers, along with the limited implementation of innovative learning models and media. The main objective of this study was to examine and analyze the effect of implementing a problem-based learning model integrated with Wordwall media on the learning outcomes of fifth-grade students at SDN 015 Samarinda Ulu. This research was classified as a quantitative experimental study using a Non-Equivalent Control Group Design. The research subjects consisted of 54 students divided into two groups: an experimental class (V A) and a control class (V B). The instruments used to measure learning outcomes were pretest and posttest questions, which had undergone empirical validity testing, including validity, reliability, item difficulty, and discrimination index tests. Inferential data analysis was conducted through a series of statistical tests, namely normality and homogeneity tests, followed by hypothesis testing using a non-parametric sample t-test. The findings revealed a significant difference in learning outcomes between the experimental group, which received the problem-based learning model integrated with Wordwall media, and the control group, which was taught using conventional methods. This difference was indicated by the statistically higher mean posttest score of the experimental group compared to that of the control group. The significance value obtained from the sample t-test was 0.008, which is lower than the predetermined significance level (α = 0.05). Therefore, it can be concluded that the implementation of the problem-based learning model supported by Wordwall media had a positive and significant effect on the learning outcomes of fifth-grade students at SDN 015 Samarinda Ulu in the topic of fractions.